The Effects of Nasal Septum Deviation on Ocular Examination Findings: Does Deviated Nasal Septum Cause Impaired Vision? - Yusuf Dündar; İlhan Ünlü; Kuddusi Teberik; Abdullah Belada; Fatih Alper Akcan (Düzce Tıp Fakültesi Dergisi, 2022)
Aim: Nasal obstruction due to nasal septum deviation is associated with systemic diseases such as cardiopulmonary disease, neurological and vascular problems. But the effect of pure nasal deviation on the ocular system has not been precisely investigated. The aim of this study was to analyze the association of nasal septal deviation with ocular examination findings. Material and Methods: Twenty-seven adult patients underwent septoplasty and 31 controls were included in the study. The study group was conducted on patients with pure nasal septum deviation which is significantly obstructing the nasal airway (>50%). In ophthalmological examination; peripapillary retinal nerve fiber layer, macular and choroidal thickness measurements were obtained. The examination findings were compared between the study and control groups. Results: The mean macular thicknesses at nasal-500μm were 305.89±32.79 and 287.87±25.00 in the study and control groups, respectively (p=0.021). The mean macular thicknesses at nasal-1000μm were 353.04±21.28 and 341.16±17.97 in the study and control groups, respectively (p=0.025). The mean thickness of choroid was statistically significantly different at central (p=0.036) and peripheral measurements; nasal-500μm (p=0.020); nasal-1000μm (p=0.001); nasal-1500μm (p<0.001); temporal-500μm (p=0.023) and temporal-1000μm (p=0.045). No statistically significant difference was found between the two groups according to ocular tension, thickness of cornea, keratometry, anterior chamber depth, axial length of cornea, and retinal nerve fiber layer thickness. Conclusion: This is one of the pioneer studies evaluating the ocular examination findings in patients with nasal septum deviation. Our results indicate the increased thickness of both macula and choroid in patients with nasal septum deviation.